First of all, you need to change the base of the logarithm: since 4=2^2, you have that
log_4(x) = log_2(x)/log_2(4) = log_2(x)/2
So, the equation becomes
log_2(x-1) = log_2(x+1)/2
Which is equivalent to
2log_2(x-1) = log_2(x+1)
Since alog(x)=log(x^a), the equation becomes
log_2((x-1)^2) = log_2(x+1)
Which is true if and only if (x-1)^2=x+1, which means
x^2-2x+1=x+1 \to x^2-3x=0.
This equation is solved by x=0 and x=3, but x=0 is not acceptable, because it would lead to
log_2(-1)=log_4(1), and we can't compute logarithms of negative numbers.
As for x=3, we can see that it's ok since it leads to
log_2(2) = log_4(4), which is true because both members are equal to 1.